Harnessing blockchain-digital twin fusion for sustainable investments - Jafar, Syed Hasan; Villamarin Rodriguez, Raul; Kannan, Hemachandran 1985-; Akhtar, Shakeb; Plugmann, Philipp 1970- (Advances in finance, accounting, and economics (AFAE) book series, 2024)
The pressing challenge of aligning cutting-edge technologies with environmental sustainability has emerged as a pivotal issue. As the demand for green investment strategies intensifies, the need for a comprehensive understanding of how to integrate blockchain and digital twins into financial practices becomes increasingly urgent. The disconnect between these innovative technologies and sustainable finance practices is a gap that, if left unbridged, hampers progress toward a more environmentally responsible financial future.Harnessing Blockchain-Digital Twin Fusion for Sustainable Investments emerges as the solution to this critical problem. This book serves as a transformative guide, offering a deep dive into the synergy of blockchain and digital twins, providing real-world applications, case studies, and strategy frameworks. Tailored for academia, finance professionals, technologists, policymakers, and company leaders, this book bridges the gap between cutting-edge technologies and sustainable finance practices. It not only contributes to ongoing research but also acts as a catalyst for innovation, empowering individuals to make informed decisions in an evolving financial landscape with a heightened commitment to environmental responsibility. Embark on a journey with this groundbreaking resource, where technology meets sustainability, and discover how to reshape finance for a greener and more innovative future.